INTEGRATION OF QUR'AN VALUES IN DAWAH MANAGEMENT: A SYSTEMATIC REVIEW OF THE LETTER AN-NAḤ VERSE 125 - Nuruzzaman, Moh. Agil; Roa'zah, Nandipah; Muazaroh, Muslimatun Diana; Afifah, Diana Elfiyatul; Sukirno, Sukirno; Supeno, Supeno; Munahar, Munahar; Lestari, Puji (West Science Islamic Studies, 2023)
This study is a systematic review of the literature related to the integration of da'wah values ​​in Surah An-Naḥl verse 125 with a modern management framework. Using the PRISMA method, 50 selected studies from 2014–2024 were analyzed thematically to identify patterns of interpretation, application, challenges, and directions for scientific development. The results indicate that the three principles of the Qur'an al-ḥknowledge, knowledgeẓAh Al-ḥasanah, and al-mujādalah bi-allatī hiya aḥThe principles of Islamic da'wah have been recontextualized and integrated with the POAC (Planning, Organizing, Actuating, Controlling) management function, thus giving rise to the Value-Based Islamic Management approach. These studies demonstrate the application of Qur'anic principles in various contemporary da'wah contexts, particularly digital da'wah, Islamic education, community empowerment, and organizational management. However, existing research is still dominated by conceptual studies with limited empirical evidence, evaluation instruments, and minimal focus on marginalized groups such as people with disabilities. This study offers an integrative conceptual framework to strengthen the formulation of values-based da'wah management theory and encourage more rigorous empirical research. These findings are expected to enrich da'wah management theory, strengthen institutional practices, and be considered in the development of inclusive and adaptive da'wah policies.